2015
DOI: 10.1186/s40621-015-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

Restriction in functioning and quality of life is common in people 2 months after compensable motor vehicle crashes: prospective cohort study

Abstract: BackgroundWe sought to identify the role of pre-injury socio-demographic and health characteristics, and injury severity in determining health-related quality-of-life outcomes for mild to moderate injuries 2 months after a motor vehicle crash in a compensable setting.MethodsPeople aged 17 years and older, injured with a New Injury Severity Score of 8 or less, in a motor vehicle crash in New South Wales and who had registered a claim with the Compulsory Third Party Insurance scheme from March to December 2010 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
3
23
2
Order By: Relevance
“…Regarding the demographic variables, there was no signi cant relationship between age or sex and the QOL of the injured participants in the present study. This is consistent with the results of other studies (11,32). Yet, our results were inconsistent with the results of cohort studies conducted in France and Australia where injured adults (usually above 35 years old) had a poorer QOL in comparison with young people (14,33), and comparison with men; women had a poorer QOL (10).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Regarding the demographic variables, there was no signi cant relationship between age or sex and the QOL of the injured participants in the present study. This is consistent with the results of other studies (11,32). Yet, our results were inconsistent with the results of cohort studies conducted in France and Australia where injured adults (usually above 35 years old) had a poorer QOL in comparison with young people (14,33), and comparison with men; women had a poorer QOL (10).…”
Section: Discussionsupporting
confidence: 94%
“…Differences in the target group may be one of the reasons for this inconsistency. In an Australian study (11), patients who were hospitalized for more than seven days and those with severe injuries were excluded;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a review have shown that ever since their accident or after being discharged from the hospital, the QOL of traffic accident victims begins to reduce and relationship between age or sex and the QOL of the injured participants in the present study. This is consistent with the results of other studies (10,22). Yet, our results were inconsistent with the results of cohort studies conducted in France and Australia where injured adults (usually above 35 years) had a poorer QOL in comparison to young people (23, 24) and in comparison to men, women had a poorer QOL (9).…”
Section: Discussionsupporting
confidence: 94%
“…A considerable volume of literature exists on the QOL of the victims of RTIs as it has been thoroughly investigated (7)(8)(9)(10)(11)(12) though when it comes to the QOL of injured motorcyclists of accidents, the conducted research is much less. Therefore, the aim of this study was to investigate the QOL of injured motorcyclists in a time period of three months after their accident to detect the factors that influence it.…”
mentioning
confidence: 99%